INFLUENCE OF MAKRO ECONOMIC, INVESTMENT DECISIONS, OWNERSHIP, TO RISK MANAGEMENT, FINANCIAL DECISIONS, AND STOCK RETURN, MODERATED BY GOOD FINANCIAL GOVERNANCE IN LQ 45 INDEX INDONESIA STOCK EXCHANGE - ., Sutinem; Ratnawati, Tri; Moehaditoyo, Srie Hartutie (Archives of Business Research, 2019)
This study aimed to determined the effect of makroeconomic, investment decisions, the ownership, on risk management , financing decisions and stock return, moderated by Good Financial Governance in LQ 45 index Indonesia Stock Exchange.The sample in the study companies that are continuously listed in the LQ 45 index Indonesia Stock Exchange 2014-2016 periode, Determination of sample is done by purposive sampling method and obtained sample of 24 companies. Method of data processing is using PLS. The result of the study were (1) makroeconomic influence negative and significantly to stock return, (2) Macroeconomic influence negative and significantly to risk management, (3) Macroconomic influence negative and significantly to financial decisions, (4) investment decisions influence positive and significantly to stock return, (5) investment decisions influence negative and significantly to risk management, (6) investment decisions influence negative and significantly to financial decisions, (7) ownership influence positive and significantly to stock return, (8) ownership influence negative and significantly to risk management, (9) ownership influence negative and significantly to financial decisions, (10) risk management positive and no significantly to stock return, (11) risk management influence positive and significantly to financial decisions, (12) financial decisions influence positive and significantly to stock return, (13) good financial governance influence positive and no significantly moderate risk management to stock return, (14) good financial governance influence positive and significantly moderate financial decisions to stock return.